Characteristics of the State Bureau of Investigation’s territorial departments’ powers - R. I. Bohdanov (Bulletin of Kharkiv National University of Internal Affairs)
The article focuses on the fact that the creation of the State Bureau of Investigation of Ukraine was an important step towards ensuring the high-quality and efficient functioning of the entire law enforcement sector of our country, as well as the establishment of the rule of law and legality. It is argued that in the current context, the State Bureau of Investigation is beginning to play an increasingly important role in ensuring the proper functioning of all other state institutions. It is emphasised that the work of the State Bureau of Investigation directly depends on the quality and effectiveness of the powers of its territorial offices.